THE INFLUENCE OF ORGANIZATIONAL COMMITMENT AND EMPLOYEE ENGAGEMENT ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS THE INTERVENING VARIABLE IN THE LHOKSEUMAWE MAYOR'S OFFICE. - Aulia, Misnatul; Jullimursyida, Jullimursyida; Puteh, Anwar (J-MIND (Jurnal Manajemen Indonesia), 2024)
This research examines the influence of organizational commitment and employee engagement on employee performance, with job satisfaction as an intervening variable. The research sample consists of 124 employees of the Lhokseumawe Mayor's Office. The analytical tool used is Structural Equation Modeling (SEM) employing the AMOS (Analysis of Moment Structure) Version 24 software. The research findings indicate that organizational commitment does not directly affect satisfaction but significantly impacts employee performance. Employee engagement, on the other hand, significantly affects job satisfaction and employee performance. Furthermore, job satisfaction influences employee performance. While job satisfaction does not mediate the influence of organizational commitment on employee performance, it has a mediating role in the relationship between employee engagement and employee performance. These findings are expected to provide a basis for formulating organizational policies related to employee management to enhance service performance in government organizations, particularly within the Lhokseumawe Mayor's Office.